Conceptual-analytical framework for exploring culture in EFL coursebooks: Analysis of teaching materials from a multimodal perspective. Issue 1 (2023) - Lavrenteva, Evgenia; Orland-Barak, Lily
Abstract: Employing literature on coursebook analysis and evaluation and informed by the research on multimodality in language teaching materials, this study proposed a conceptual-analytical framework for exploring how cultural meaning is conveyed in foreign language teaching materials through the way in which text, task, and image combine in a learning activity. Through the application of the proposed framework, we explored cultural representations found in texts, students' meaning-making opportunities guided by tasks as well as alignments and potential contradictions between verbal and visual messages by analysing images. In doing this, we attempted to evaluate the potential of language teaching materials to cater for diverse groups of learners within a given socio-cultural context. In our investigation, we drew on two types of coursebook evaluation - micro-evaluation and macro-evaluation - which were supplemented by the deductive content analysis. We illustrate how the proposed framework might help teachers evaluate the effectiveness of coursebooks' use of multiple representations to support student learning and meaning-making. Highlights: A framework for exploring how cultural meaning is conveyed in foreign language teaching materials has been proposed. The framework was illustrated through a micro-evaluation and a macro-evaluation of a set of teaching materials. The materials differ in cultural content, opportunities for cultural comparison and types of classroom activities. The kind of information that is left out or presented in a way that misconstrues reality sets the stage for cultural bias. Recommendations in the field of materials development and enactment are suggested.